COUNSELING ON TAX UNDERSTANDING AND ITS PROFITS FOR FOOD AND BEVERAGE MICRO, SMALL AND MEDIUM ENTERPRISES (MSMEss) UNDER THE GUIDELINES OF DMI GRESIK IN GRESIK REGENCY - Asyik, Nur Fajdrih; Priyadi, Maswar Patuh; Triyonowati, Triyonowati; Respatia, Wimba; Yahya, Yahya (IJCDE (Indonesian Journal of Community Diversity and Engagement), 2023)
The purpose of this community service is to solve the problems found in MSMEs Partners assisted by DMI Gresik Regency, namely an understanding of tax objects and tax subjects, an understanding of the basic principles of MSMEs Final PPh, and an understanding of tax reporting. Related to this, a solution is provided by providing an understanding of taxation in DMI-assisted MSMEs in Gresik Regency The counseling method is carried out by the lecture method and the practice of direct calculations. It is hoped that this training can help MSMEs actors in understanding taxation. The results of the dedication carried out: (1) MSMEs partners can understand the difference between tax objects and tax subjects (2) MSMEs partners can calculate MSMEs Final Income Tax (3) MSMEs partners can report tax returns. Thus it will encourage a sustainable national economy.